Fatini Nasuha, recipient of UMPSA Royal Education Award, wins PSWM Outstanding Female Student Award - Naqiah, Puaad (UMPSA, 2025)
KUALA LUMPUR, 16 May 2025 – Fatini Nasuha Ahmad Puad, a graduate with a Bachelor of Technology in Manufacturing Engineering (Pharmaceuticals) with Honours from the Faculty of Chemical and Process Engineering Technology (FTKKP), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), was recently named the recipient of the 2025 Outstanding Female Student Award by the Malaysian Graduate Women Association (Persatuan Siswazah Wanita Malaysia, PSWM).